硬齿面齿轮滚挤技术及有限元分析 - 任志刚; 郑鹏 (Jixie chuandong)
A ausform-finishing process,which integrates the technology of heat treatment,hardening of steel components and tooth profile machining into a manufacturing operation,is discussed,and the machining principle of Ausform-finishing is represented.Then the gear steel 20CrMo which is widely used in auto and precise machine industry is analyzed by ANSYS software.A better basis for the experimental investigation of this technology is provided.